Downregulation of microRNA-196a inhibits stem cell self-renewal ability and stemness in non-small-cell lung cancer through upregulating GPX3 expression. (October 2019) - Liu, Qin; Bai, Wei; Huang, Fang; Tang, Jian; Lin, Xiang
Abstract: Studies have reported a high expression profile of microRNA-196a (miR-196a) in many cancers, which potently plays important roles in carcinogenesis. However, the involvement of miR-196a in affecting non-small cell lung cancer (NSCLC) carcinogenesis still remains uncertain. NSCLC-related differentially expressed genes were retrieved for this study according to the microarray-based analysis, which demonstrated that miR-196a may be involved in NSCLC progression via regulation of the JunN- terminal kinase (JNK) pathway by targeting glutathione peroxidase 3 (GPX3). Hence, this study aimed to explore the relationship among miR-196a, GPX3, and the JNK pathway and to investigate its functional regulations in NSCLC. Initially, highly-expressed miR-196a and lowly-expressed GPX3 were determined in NSCLC tissues and cells. Next, the NSCLC cells were manipulated with a series of mimic, inhibitor or shRNA to investigate the impact of miR-196a and GPX3 on CSC viability, proliferation, self-renewal ability and stemness. The in vivo effect of miR-196a was measured in nude mice xenografted with NSCLC cells. The results demonstrated that downregulation of miR-196a and restoration of GPX3 inhibited CSC viability, proliferation, self-renewal ability, stemness and tumorigenicity. Meanwhile, the underlying relationship among miR-196a, GPX3 and JNK pathway was explored by treatment with the JNK pathway inhibitor (SP600125), or sh-GPX3. Downregulated miR-196a and upregulated GPX3 could elevate the GPX3 protein expression and reduce the extent of JNK and c-Jun phosphorylation. Taken together, miR-196a promotes the development of NSCLC via activation of the JNK pathway through down-regulation of GPX3 and serve as a potential therapeutic target in NSCLC.